Persepsi Siswa terhadap Pelayanan Usaha Kesehatan Sekolah (UKS) di Sekolah Menengah Kejuruan (SMK) Teknik Negeri Kota Padang - Fitri Cahyanti Cahyanti; Jasrial Jasrial; Rusdinal Rusdinal; Ermita Ermita (Universitas Negeri Padang, 2021)
One of the special education services in schools is school health services or commonly referred to as School Health Enterprises, hereinafter abbreviated as UKS. Which is the purpose of the UKS service, namely to provide health services to students who come to receive health services from school health officials. The purpose of this research is that the author wants to find data related to student views on UKS services at Padang City State Engineering Vocational Schools for the 2019/2020 year of entry as many as 2,085 people. The sample was determined by using the stratified proportional random sampling technique and obtained a sample of 97 respondents. Data were collected in this study by means of a questionnaire that had been tested for validity and reliability. Data were analyzed using the formula mean (mean). Obtaining data analysis shows that the views of students on the School Health Business services provided by UKS officers at the State Technical Vocational School of Padang City can be seen from the indicator (1) the service time gets a good scale, namely at the number 3.92. (2) the service procedure obtained a good scale, namely at 3.99. (3) politeness obtains a good scale, namely at the number 4.04. (4) reliability of obtaining a good scale, namely at the number 4.02. (5) service certainty gets a good scale, namely at 3.99. It can be concluded that the students' views on the School Health Business services at the State Technical Vocational School of Padang City showed a good scale, namely obtaining a score of 3.99.